Hi guys, find all complex numbers satisfying `z^6-1=0.`

I have seen someone do the working out as follows:  


`z^6-1=(z^3-1)(z^3+1) = (z-1)(z^2+z+1) (z+1)(z^2-z+1).`


However, I am not sure what the next step is.



Expert Answers

An illustration of the letter 'A' in a speech bubbles

Because of the factors `z-1` and `z+1,` we know that `+-1` are solutions.

Now we can use the quadratic formula for the remaining factors. For

`z^2+z+1,` we get

`z=(-1+-sqrt(1^2-4(1)(1)))/2=(-1+-i sqrt(3))/2`

and for `z^2-z+1` we get

`z=(1+-i sqrt(3))/2` .

The six solutions are `+-1,(-1+-i sqrt(3))/2,(1+-i sqrt(3))/2.`

Note that if `z` is a solution, then so is ``the conjugate of `z.` This is true for any solution of `z^n=1` for any `n.` Also, if `z` is a solution, so is `-z.` This is the case for the solutions of `z^n=1` only when `n` is even (which is why it works for this example).

See eNotes Ad-Free

Start your 48-hour free trial to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Get 48 Hours Free Access
Approved by eNotes Editorial